Danlou Tablet Activates Autophagy of Vascular Adventitial Fibroblasts Through PI3K/Akt/mTOR to Protect Cells From Damage Caused by Atherosclerosis - Wang, Li; Wu, Tong; Si, Chunying; Wang, He; Yue, Ke; Shang, Shasha; Li, Xiaohui; Chen, Yushan; Guan, Huaimin (Frontiers in Pharmacology, 2021)
Danlou tablet (DLT), a commercial Chinese patent medicine, has been widely used to treat cardiovascular diseases for many years. Atherosclerosis (AS) is the leading cause of cardiovascular disease. Increasing evidence indicates that autophagy plays a vital role in the development of AS. Here we investigated whether DLT could activate autophagy to improve AS and further clarified its underlying mechanisms. In an ApoE-/- mice model, the results of Oil red O, Masson’s trichrome, and H&E staining techniques showed that DLT significantly inhibited lipid accumulation and fibrosis formation in atherosclerotic plaque tissue. DLT also inhibited serum triglyceride, cholesterol, and low-density lipoprotein levels and suppressed serum levels of inflammatory factors interleukin-6 and tumor necrosis factor-α in ApoE-/- mice. Moreover, DLT suppressed proliferation, migration, and invasion of human vascular adventitial fibroblasts (HVAFs) by inhibiting the PI3K/Akt/mTOR pathway. In addition, western blot analysis showed that Danlou tablet treatment decreased the expression of p62 and increased Beclin 1 and LC3 I -to-LC3 II ratios in HVAFs. The role of autophagy in treating atherosclerosis by DLT is confirmed by 3-methyladenine (autophagy inhibitor) and rapamycin (autophagy activator) in HVAFs. In summary, DLT activated PI3K/Akt/mTOR-mediated autophagy of vascular adventitial fibroblasts to protect cells from damage caused by atherosclerosis.